Tumour-like presentation of atypical posterior reversible encephalopathy syndrome with prominent brainstem involvement - Di Stefano, Vincenzo (BMJ Case Rep, 2020)
Typical posterior reversible encephalopathy syndrome (PRES) is a clinical-neuroradiological entity characterised by bilateral white matter oedema, which is usually symmetrical and totally reversible in 2–3 weeks. A 46-year-old man presented with a persistent headache and visual blurring in the right eye. On admission, the clinical examination revealed minimal unsteadiness of gait and elevated blood pressure. A brain MRI showed a hyperintense signal on T2-weighted sequences in the whole brainstem, extended to the spinal cord (C2–C6), the left insula and the right cerebellum. When his blood pressure was controlled, his symptoms gradually improved. The follow-up MRI scan at 3 weeks revealed a dramatic regression of the hyperintense lesions on T2-weighted sequences. The differential diagnosis of PRES is very wide, especially in the case of conspicuous brainstem involvement. Treatable causes of white matter oedema should be always kept in mind to avoid misdiagnosis and prevent complications, such as intracranial haemorrhage.